Anterior Cruciate Ligament Reconstruction Improves Functional Scores and Quality of Life in Patients Older Than 50 Years of Age - Batuhan Çokyaşar, M.D; Ozan Altun, M.D; Uygar Daşar, M.D (Elsevier, 2023)
Purpose: To evaluate quality of life changes and functional outcomes of anterior cruciate ligament reconstruction in patients older than 50 years of age with anterior cruciate ligament injury. Methods: Patients who were older than 50 years of age and had undergone anterior cruciate ligament reconstruction with single-bundle hamstring tendon auto graft surgery between January 2016 and February 2018 were identified. Preoperative Tegner activity scores, Lysholm knee scores, International Knee Documentation Committee (IKDC) 2000 scores, and Short-Form 36 scores were compared with results that were documented 1 year after surgery. Results: A total of 35 patients were included (20 male/15 female; mean age 52 years [range 50-59 years]). Patients' preoperative mean Tegner score was 1.48. Mean Tegner score at 1-year follow-up was 3.82. Preoperative mean Lysholm score was 45.8. Postoperative mean Lysholm score was 88. Preoperative mean IKDC 2000 score was 33. Postoperative mean IKDC 2000 score was 82. All of these changes were statistically significant (P < .05). All of the parameter changes at Short Form-36 except for role limitations due to emotional problems were statistically significant. Conclusions: Improved functional knee scores, quality of life, and psychological status were achieved at anterior cruciate ligament reconstruction in patients older than 50 years of age. Level of Evidence: Level IV, therapeutic case series.